Guía del investigador americanista : Mérida, Venezuela - Edda S. O. Samudio A.; Ebert Cardoza S. (Nuevo mundo - Mundos Nuevos, 2013)
The city of Mérida, funded in 1558 by Captain General Juan Rodríguez Suárez, is situated on a large and beautiful hillside of the río Chama valley. According to the 2011 census, it has 221.879 inhabitants, which is 28% of Mérida state's total population (826.720). Its total Metropolitan area includes 345.489 individuals. Mérida has been an educational center since early Hispanic times and hosts the famous and bicentenary Universidad de los Andes, which has been a central landmark in its history and identity as a studious city, between colonial remains and a lively student atmosphere. Mérida also counts an Arzobispado, the San Buenaventura de los Caballeros de Mérida seminary, numerous libraries, museums, parks and the world's highest telepheric (also the second longest in the world) : those are only a few of the numerous monuments that make it a cultural and touristic hub in Venezuela.